MENGEMBANGKAN MINAT DAN BAKAT SISWA MELALUI KEGIATAN EKSTRAKURIKULER - Maria Goreti Eko; Flora Nidia Meo; Anggelina Amus; Regina Odje; Nikodemus Bate (STKIP Subang, 2026)
This study aims to examine how extracurricular activities contribute to the development of students’ interests and talents within the school environment. Extracurricular activities serve as a strategic platform for exploring students’ potential beyond the scope of intraclass learning. The research employed a descriptive qualitative approach, using data collection techniques such as observation, interviews, and documentation. The study participants included students, extracurricular activity supervisors, and the principal of a public junior high school. The results show that extracurricular programs such as scouting, traditional dance, choir, and sports significantly enhance students’ active participation, self-confidence, and social skills. Moreover, these activities provide opportunities for students to express their interests and cultivate their talents according to their individual potentials. The study recommends that schools place greater emphasis on structured and continuous extracurricular development as an integral part of character building and non-academic achievement.